2022
DOI: 10.1177/15589250221081856
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole coating on aramid fabrics for improved stab resistance and multifunction

Abstract: As an epoch of intelligent clothing is coming, soft body armor is required to possess not only improved mechanical performance but more functions, such as electronic conductivity, anti-ultraviolet capability, electrical heating property, etc. In this work, polypyrrole (PPy) is coated on Twaron fabrics to enhancing their stabbing resistance and simultaneously endowing them with multifunction. The resultant PPy-coated Twaron fabric exhibits better tensile strength. The strength of the PPy-coated fiber is increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The composite prepared in this study exhibited a significant improvement in the maximum quasi-static peak puncture resistance force (267.6 N) compared to the pure aramid fabric (15.61 N), with an increase of 1614.29%. This improvement surpasses the puncture resistance performance of other composites, such as PPy/Twaron, 11 TPU/silica/STF/aramid, 12 TPU/silica/nonwovens, 13 TPU/polyester nonwo-vens, 14 STF/aramid, 15 and SiC/STF. 19 Moreover, the puncture-resistant composites developed in this study also demonstrated excellent resistance to strong acids and bases, surpassing other composites such as fluoropolymer/silica hybrids, 50 PVDF-HFP/FAS/WPU, 47 PTFE, and FAS for chemical protection, 51 PTFE/silica-coated fabrics, 52 and F− SiO 2 @AP coatings.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The composite prepared in this study exhibited a significant improvement in the maximum quasi-static peak puncture resistance force (267.6 N) compared to the pure aramid fabric (15.61 N), with an increase of 1614.29%. This improvement surpasses the puncture resistance performance of other composites, such as PPy/Twaron, 11 TPU/silica/STF/aramid, 12 TPU/silica/nonwovens, 13 TPU/polyester nonwo-vens, 14 STF/aramid, 15 and SiC/STF. 19 Moreover, the puncture-resistant composites developed in this study also demonstrated excellent resistance to strong acids and bases, surpassing other composites such as fluoropolymer/silica hybrids, 50 PVDF-HFP/FAS/WPU, 47 PTFE, and FAS for chemical protection, 51 PTFE/silica-coated fabrics, 52 and F− SiO 2 @AP coatings.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…In order to accomplish the aforementioned objectives, researchers have conducted extensive research in this field. The current approach to achieve a combination of puncture resistance and flexibility involves the use of inorganic/organic hybrid coatings, such as shear thickening fluid (STF), hydrogels, and resins, in conjunction with high-performance fibers such as Poly-p-phenylene benzobisoxazole (PBO), carbon, or aramid fibers. , Wang et al reported a thermoplastic polyurethane (TPU) material with an ultrahigh toughness and good impact resistance, which is one of the most promising materials in the field of personal protection . Additionally, the puncture and cut resistance of these composites can be greatly enhanced by modifying parameters such as the type of nanoparticle fillers, contents, and particle sizes .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, different polymers can be used to glue the fibers or filaments of a textile fabric together and thus increase the fiber/fiber friction, leading to improved stab resistance [ 68 , 69 , 70 ]. On the other hand, many textile fabrics with a coating of silica or other ceramic materials are reported as lightweight stab resistance materials.…”
Section: Reinforced Polymers and Composites For Stab Resistancementioning
confidence: 99%
“…Therefore, fiber surface modification improves the interfacial bonding properties with the resin matrix 7,8 . Depending on different modification principles, the commonly used modification methods include plasma treatment, 9,10 surface coating treatment, 11,12 surface grafting, 13,14 and acid–base etching 15,16 . High‐energy particle treatment requires reasonable process control, and surface etching often causes a loss of fiber strength.…”
Section: Introductionmentioning
confidence: 99%
“…principles, the commonly used modification methods include plasma treatment, 9,10 surface coating treatment, 11,12 surface grafting, 13,14 and acid-base etching. 15,16 High-energy particle treatment requires reasonable process control, and surface etching often causes a loss of fiber strength.…”
mentioning
confidence: 99%